The Impact of User-Generated Content and E-WOM on Purchase Decisions for XYZ Products on the Tiktok Application in Malang City - Barreto Lay, Piter; Indriani, Sri; Rupianti, Reni (Journal Research of Social Science, Economics, and Management, 2026)
The rapid development of social media, particularly TikTok, has transformed consumer behavior in seeking information and making purchasing decisions. TikTok not only serves as an entertainment medium but also as a digital marketing platform that features user experience-based content. This condition has encouraged the emergence of User-Generated Content (UGC) and Electronic Word-of-Mouth (E-WOM) as forms of digital communication that are considered more authentic and trustworthy by consumers, particularly Generation Z as the platform's dominant user base. The high level of user interaction with XYZ product content on TikTok indicates the potential influence of UGC and E-WOM on purchase decisions, although findings from previous studies remain inconsistent. This study aims to determine the effect of UGC and E-WOM on purchase decisions for XYZ products on the TikTok application in Malang City. This study adopts a quantitative approach using a survey method. Data were collected through an online questionnaire via Google Forms, distributed to TikTok users from Generation Z in Malang City who had viewed and interacted with XYZ product content. The sampling technique employed was purposive sampling, with a total of 143 respondents. Data analysis was conducted using multiple linear regression with the aid of the Statistical Package for the Social Sciences (SPSS) application. The results indicate that UGC and E-WOM have a positive and significant effect on purchase decisions for XYZ products. Simultaneously, UGC and E-WOM also exert a significant combined influence on purchase decisions, with UGC emerging as the most dominant variable.